Are "fair" wages quantitatively important for business cycle fluctuations in Bulgaria? - Aleksandar Vasilev (Review of Economic Perspectives, 2020)
We introduce "fair" wages in a general-equilibrium model where worker's effort is unobservable and investigate whether such a mechanism can quantitatively account for the degree of real wage rigidity in the Bulgarian labor markets, as documented in Lozev, Vladova, and Paskaleva (2011) and Paskaleva (2016). In contrast to Danthine and Kurmann (2004), we internalize the effect that past wages have on the current effort level. We calibrate the model to Bulgarian data (1999-2016), and quantify the effect of technological shocks on hours and wages in the theoretical setup. Overall, the calibrated model with "fair" wages performs poorly when it comes to the relative volatilities of labor market variables. This is because aggregate labor market conditions, as proxied by the employment rate and past aggregate wages, turn out not to be quantitatively important for business cycles in Bulgaria.
Keywords: E24; E32; J41; 330; Business cycles; unobservable effort; fair wages; unemployment; Bulgaria